The Effect of Distribution Strategy on Cigarette Product Availability in Traditional Retail Stores - Muhammad Reza Rivandana; Endi Sarwoko (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study aims to examine the effects of distribution strategy and the use of distribution technology on cigarette product availability in traditional retail outlets in Jember Regency. A quantitative approach employing an explanatory and cross-sectional research design was adopted. The sample comprised 120 owners or managers of traditional retail outlets selected through purposive sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The results show that distribution strategy has a positive and significant effect on product availability, with a path coefficient of 0.943, a t-statistic of 24.940, and a p-value of less than 0.001. In contrast, the use of distribution technology has a negative path coefficient of −0.075; therefore, the hypothesis proposing a positive effect of distribution technology use on product availability is not supported. The coefficient of determination (R2) of 0.780 indicates that distribution strategy and the use of distribution technology jointly explain 78% of the variance in product availability. These findings demonstrate that delivery consistency, distributor–retailer relationships, distribution coverage, and order fulfillment accuracy play a more substantial role in maintaining product availability than the independent use of technology. Distribution technology should therefore be integrated with accurate inventory data, reliable order fulfillment processes, and responsive distributor services to provide more optimal operational benefits.